Cognitive-behavioural factors associated with adherence to antiretroviral medication among HIV infected patients in Ibadan, Oyo state - Akinoye, John I.; Amosu, Ademola M.; Amodemaja, Omotayo A. (International Journal Of Community Medicine And Public Health, 2020)
Background: The initiation of antiretroviral therapy has brought about a huge transformation in HIV care and it has helped in saving millions of lives since its inception. Nevertheless, non-adherence poses a huge challenge to HIV care as this exposes the patients to opportunistic infections and brings about highly resistant viral strains. Therefore, this study assessed the cognitive-behavioural factors associated with the adherence to antiretroviral medication among HIV infected patients in Ibadan, Oyo State, Nigeria. Methods: A descriptive cross sectional study design guided by a behavioural theory was employed. Multistage sampling was employed in this study. Purposive sampling was used to select the hospitals and simple random sampling was used to select the respondents. A 42 item semi-structured questionnaire validated at 0.85 Cronbach alpha was used. Data were analysed using descriptive and inferential statistics at p<0.05. Results: The result showed a mean age of 42.11±11.60 years, while 238 (82.6%) of the respondents were female. The study revealed a positive attitudinal disposition of 54% and a negative perception of 51.5%. Optimal antiretroviral medication adherence among the respondents was 189 (65.6%). Attitude and perception showed a statistical correlation towards antiretroviral medication adherence where p=0.001 and p=0.000 respectively. Conclusions: Attitude and perception are major cognitive-behavioural factors that predicts antiretroviral medication adherence, hence, health promotion intervention that could modify these factors and improve antiretroviral medication adherence is highly recommended.